Association Between First Episode Schizophrenia, Metabolic Syndrome and Insulin Resistance-Related Proteins in Female Balb/C Mice: - Sattar, Haseeb; Li, Huqun; Han, Yong; Zhou, Hong; Darbalaei, Sanaz; Li, Weiyong (Galen Medical Journal, 2018)
Background: Metabolic syndrome is a group of different disorders mainly includes, insulin resistance, obesity, cerebrovascular disorders, dyslipidemia, which leads to increase mortality. Patients suffering from related psychotic disorders such as schizophrenia are at the higher risk of developing metabolic syndrome. The aim of this study was to evaluate the association between the first episode of schizophrenia, metabolic syndrome and insulin resistance-related proteins in blood and adipose tissue of mice. Materials and Methods: Twelve, female Balb/c mice were randomly divided into two groups; one group was injected intraperitoneal MK-801 (0.6mg/kg/d) to induce schizophrenia, and other group received the 0.9% normal saline for two weeks. Body weight, fasting blood glucose (FBG), oral glucose tolerance (OGT), and Homeostatic model assessment (HOMA), were observed. Blood and adipose tissue were collected and Western blotting was done to evaluate the insulin resistance related proteins (GGPPS, FAT, PTP-1B, GRK2, ATGL, FGF21, and PGC-1α) by using GAPDH as an internal standard. Results: There was a significant increase in mean body weight in schizophrenic group (21.76 vs 22.81, P=004). On day 14, the FBG, insulin concentrations and Homeostatic model assessment and insulin resistance (HOME-IR) were high in schizhphrenic group vs control group, e.g. 5.3±0.6 vs 3.47±0.2 (P=0.0001), 28.9±2.2 vs 23.3±0.6 (P<0.005) and 9.2±1.3 vs 3.9±0.2 (P=0.0001) . Impaired glucose tolerance deranged from 4.8mmol/L to 6.4mmol/L. Western blotting showed a marked increase in the expression of GGPPS, FAT, ATGL, and FGF21 proteins in monocytes and PTP-1B, GRK2, and PGC-1α ratios in adipose tissues. Conclusion: There was a positive relation between schizophrenia and metabolic syndrome e.g. insulin resistance and obesity. Certain proteins in adipocytes and blood were responsible for causing insulin resistance. [GMJ.2018;7:e692]